2010
DOI: 10.1080/10584587.2010.492014
|View full text |Cite
|
Sign up to set email alerts
|

Nanosized High κ Dielectric Material for FINFET

Abstract: In this paper, Zirconium dioxide nanoparticle has been synthesized using wet chemical methods at room temperature. The structural characterization (SEM / X-ray Diffraction) of the nanoscaled Zirconium Dioxide is discussed in this paper. The particle size of the ZrO 2 is observed in the range of 50-100 nm. It is expected that both the nanoscaling and the high dielectric constant of ZrO 2 would be an advantage while fabricating a FET. The conventional dielectric SiO 2 used for gate , with a dielectric constant o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 5 publications
(2 reference statements)
0
15
0
Order By: Relevance
“…A figure of merit to judge a highgate dielectric layer is the equivalent oxide thickness (EOT) = ( SiO 2 / high-)d . If a dielectric material with a higher dielectric constant (high-) can replace SiO 2 , the dielectric layer thickness can be increased proportionally while keeping the same gate capacitance [2,3]. Since a thicker layer is used for insulation, the tunnelling current is drastically reduced in the tunnelling region.…”
Section: Introductionmentioning
confidence: 99%
“…A figure of merit to judge a highgate dielectric layer is the equivalent oxide thickness (EOT) = ( SiO 2 / high-)d . If a dielectric material with a higher dielectric constant (high-) can replace SiO 2 , the dielectric layer thickness can be increased proportionally while keeping the same gate capacitance [2,3]. Since a thicker layer is used for insulation, the tunnelling current is drastically reduced in the tunnelling region.…”
Section: Introductionmentioning
confidence: 99%
“…The precipitate was filtered and washed with dilute HCl and demonized water repeatedly. Then the precipitate was dried at controlled atmosphere at 100 о C [75]. The outcome of this preparation given the thermally stable with nanosize Zirconium-di-oxide material is observed [75], it gives excellent improvement in the FinFET devices.…”
Section: Dry Chemical Processmentioning
confidence: 98%
“…There have been many review papers, and industry consensus that proposed a criterion for choosing alternative high-k materials for in MOSFET for different applications. [ 8,9,11,12,13,14] Its observed that Zirconiam-di-oxide is one of the alternate material for gate oxide in the FinFET [75]. Zirconia is the most appropriate metal oxide since it is thermodynamically stable with Si [15].The figure.1 shows the TEM microphotograph of nanocrystalline ZrO 2 particles prepared by hydrothermal method and stability of the material in the nanosize, since it has a dielectric constant value of 25, a large energy bandgap it is suggested for FinFET device.…”
Section: Selection Of Zirconium As High K Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…may be advantageously employed for high performance semiconductor devices [1][2][3][4] . Also the larger physical thickness t hk of the high-k dielectric reduces the parasitic gatesource/drain (G-S/D) outer fringe capacitance 5 .…”
mentioning
confidence: 99%